HUBUNGAN KUALITAS KOMPETENSI, BUDAYA ORGANISASI DAN MOTIVASI KERJA DENGAN PELAYANAN PRIMA TENAGA ADMINISTRASI SEKOLAH - Zakiyatul Ummah; Achmad Supriyanto; Sultoni Sultoni (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2018)
Abstract : The purpose of this study is to know the relationship of quality competence, organizational culture and work motivation with excellent service TAS. This research is a descriptive correlational research. The population of this study is TAS while for sampling using proportional random sampling. Data analysis used is descriptive analysis technique and double correlation. The result of the research shows that there is a significant correlation between competence quality and excellent service, there is significant correlation between organizational culture and excellent service, there is significant relation of work motivation and excellent service, there is significant correlation of competence quality, organizational culture and work motivation with excellent service TAS.Keyword : Quality of competence, organizational culture, work motivation, excellent service